A resource-optimal key pre-distribution scheme with improved security for wireless sensor networks - Dai, Tran Thanh; Pathan, Al-Sakib Khan; Hong, Choong Seon (Springer-Verlag, Berlin, Germany, 2006)
This paper proposes an efficient resource-optimal key predistribution scheme for providing improved security in wireless sensor networks. We exploit the advantages of two schemes with some modifications and combine our encoding scheme to get resource-efficiency and better security.